Grass carp SARM1 and its two splice variants negatively regulate IFN-I response and promote cell death upon GCRV infection at different subcellular locations. Issue 1 (January 2015) - Yan, Nana; Su, Jianguo; Yang, Chunrong; Rao, Youliang; Feng, Xiaoli; Wan, Quanyuan; Lei, Chuzhao
Highlights: Two novel splice variants CiSARM1s1 and CiSARM1s2 only retain ARM domain(s). CiSARM1 and CiSARM1s1 are located in mitochondria, while CiSARM1s2 resides in the whole cell. CiSARM1 inhibits GCRV-triggered IFN-I response by affecting the molecules in TRIF-, MyD88- and IPS-1-dependent pathways. CiSARM1s1 and CiSARM1s2 inhibit GCRV-triggered IFN-I response by suppressing mediators in MyD88 and IPS-1signal pathways. CiSARM1, CiSARM1s1 and CiSARM1s2 promote GCRV-induced cell death. Abstract: Sterile alpha and Toll/IL-1R motif containing 1 (SARM1) negatively regulates TRIF-dependent TLR signaling in mammals. However, its immune function remains unclear in teleost. Here, a grass carp Ctenopharyngodon idella SARM1 (CiSARM1) gene and its two novel splice variants (CiSARM1s1 and CiSARM1s2) were identified. CiSARM1s1 and CiSARM1s2 are generated by intron retention mechanism, and they only retain N-terminal HEAT/armadillo motifs. In C. idella kidney (CIK) cells, CiSARM1 and CiSARM1s1 are located in mitochondria, whereas CiSARM1s2 distributes in the whole cell. All the three transcripts are ubiquitously expressed in 15 investigated tissues. They were responsive to GCRV in vivo and in vitro and to viral/bacterial PAMPs in vitro, implying they participate in both antiviral and antibacterial immune responses. By overexpression experiment, CiSARM1 and its two isoforms affected each other's expression in CIK cells. CiSARM1 inhibited GCRV-triggered IFN-I response by affecting the expressions of CiTRIF, CiMyD88, CiIPS-1, CiTRAF6, CiTBK1, CiIRF3 and CiIRF7 in TRIF-, MyD88- and IPS-1-dependent pathways; CiSARM1s1 and CiSARM1s2 inhibited GCRV-triggered IFN-I production through suppressing the expressions of CiMyD88, CiIPS-1, CiTRAF6, CiTBK1, CiIRF3 and CiIRF7 in MyD88- and IPS-1-dependent pathways. Moreover, antiviral activity assays indicated that all the three genes promote GCRV-induced cell death. These results were further verified by RNAi experiments. Thus, CiSARM1 and its two splice variants jointly prevent excessive activation of the host immune response. These findings uncover the regulatory mechanisms of SARM1 in teleost and lay a foundation for further functional and evolutionary researches on SARM1.